1985
DOI: 10.1902/jop.1985.56.8.443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Evaluation of Therapy for Juvenile Periodontitis

Abstract: Eight patients (mean age 15.6 yrs) with severe molar-incisor bone loss and pocket formation characteristic of juvenile periodontitis were entered into a clinical protocol of three sequential stages: scaling and root planing (S/RP); S/RP concurrent with systemic tetracycline therapy (1 gm/day for 28 days); periodontal surgery concurrent with systemic tetracycline therapy. Clinical and microbiological examinations were scheduled at baseline, at 1 to 2 months after Stage I, at 1 to 2 months after completion of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(144 citation statements)
references
References 18 publications
8
135
0
1
Order By: Relevance
“…A. actinomycetemcomitans has been isolated from adult periodontitis lesions, but less frequently and in lower numbers than from lesions in juvenile periodontitis subjects (21,26). Treatment failures have been associated with the failure to reduce the amount of the microorganism in treated sites (14,17). Furthermore, data on the transmission of A. actinomycetemcomitans from host to host (5,6,32) and new evidence of its role as an infectious agent involved in disease development at extraoral sites (35) are providing one of the strongest associations between this oral pathogen and periodontal and systemic diseases.…”
mentioning
confidence: 99%
“…A. actinomycetemcomitans has been isolated from adult periodontitis lesions, but less frequently and in lower numbers than from lesions in juvenile periodontitis subjects (21,26). Treatment failures have been associated with the failure to reduce the amount of the microorganism in treated sites (14,17). Furthermore, data on the transmission of A. actinomycetemcomitans from host to host (5,6,32) and new evidence of its role as an infectious agent involved in disease development at extraoral sites (35) are providing one of the strongest associations between this oral pathogen and periodontal and systemic diseases.…”
mentioning
confidence: 99%
“…Several studies in the 80's and early 90's have demonstrated that treatment revolving solely around mechanical debridement either in the form of "closed" debridement or access flap technique did not produce satisfactory results leading to progressive attachment loss [7][8][9][10][11]. This was later attributed to the fact that pathogens associated with LAP such as Aggregatibacter actinomycetemcomitans (A.A) can penetrate tissues and therefore never completely eliminated by mechanical therapy alone [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the heterogeneity of the included studies was remarkable. Some publications dealt only with the deepest site in every patient, while others calculated with full mouth PD [54,77]. In that way "mean pocket reduction" could simply be the wrong parameter to base such a statement on.…”
Section: Discussionmentioning
confidence: 99%